Lithium secondary battery

By controlling the ten-point average roughness of the negative electrode current collector and using a pressurizing member in lithium-precipitation type lithium secondary batteries, the charge/discharge rate characteristics are improved, addressing issues of dendrite growth and overvoltage.

JP7659991B2Active Publication Date: 2025-04-10NISSAN MOTOR CO LTD +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2021010420
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-01-26
Publication Date
2025-04-10
Estimated Expiration
2041-01-26

AI Technical Summary

Technical Problem

Existing lithium-precipitation type lithium secondary batteries face challenges in achieving sufficient charge/discharge rate characteristics due to issues like dendrite growth causing internal short circuits and increased overvoltage during lithium deposition.

Method used

The implementation of a power generation element with a negative electrode current collector having a specific ten-point average roughness (R) of 3 to 50 μm, along with a pressurizing member that applies a predetermined pressure, enhances the charge/discharge rate characteristics by ensuring sufficient space for lithium metal deposition and absorbing volume changes of the negative electrode.

Benefits of technology

This configuration improves the charge/discharge rate characteristics of lithium secondary batteries by suppressing overvoltage during lithium deposition and ensuring uniform lithium metal deposition, thereby enhancing the battery's performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659991000002
    Figure 0007659991000002
  • Figure 0007659991000003
    Figure 0007659991000003
  • Figure 0007659991000004
    Figure 0007659991000004
Patent Text Reader

Abstract

To provide means for improving charge / discharge rate characteristics in a lithium deposition type lithium secondary battery.SOLUTION: A lithium secondary battery includes a power generation element including a positive electrode that has a positive electrode active material layer containing a positive electrode active material capable of intercalating and deintercalating lithium ions, a negative electrode that has a negative electrode current collector and on which lithium metal is deposited on the negative electrode current collector during charging, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, and a pressurizing member that pressurizes the power generation element in the stacking direction with predetermined pressure, and the ten-point average roughness (RzJIS) of the surface of the negative electrode current collector on the solid electrolyte layer side is controlled in the range of 3 to 50 μm.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lithium secondary battery. [Background technology]

[0002] In recent years, there has been a strong desire to reduce carbon dioxide emissions in order to combat global warming. In the automobile industry, there are high hopes for a reduction in carbon dioxide emissions through the introduction of electric vehicles (EVs) and hybrid electric vehicles (HEVs), and the development of non-aqueous electrolyte secondary batteries, such as motor drive secondary batteries, which hold the key to putting these vehicles to practical use, is being actively pursued.

[0003] Secondary batteries for driving motors are required to have extremely high output characteristics and high energy compared to consumer lithium-ion secondary batteries used in mobile phones, notebook computers, etc. Therefore, lithium-ion secondary batteries, which have the highest theoretical energy of all practical batteries, have attracted attention and are currently being rapidly developed.

[0004] Currently, lithium-ion secondary batteries in widespread use use flammable organic electrolytes as electrolytes, and for these liquid-based lithium-ion secondary batteries, stricter safety measures against leakage, short circuits, overcharging, etc. are required than for other batteries.

[0005] In recent years, therefore, research and development into all-solid-state lithium secondary batteries that use oxide- or sulfide-based solid electrolytes has been actively conducted. A solid electrolyte is a material that is mainly composed of ion conductors that can conduct ions in a solid state. For this reason, in principle, all-solid-state lithium secondary batteries do not have the various problems caused by flammable organic electrolytes that occur in conventional liquid-based lithium-ion secondary batteries. In addition, in general, the use of high-potential, large-capacity positive electrode materials and large-capacity negative electrode materials can significantly improve the output density and energy density of the battery.

[0006] Conventionally, as one type of all-solid-state lithium secondary battery, a so-called lithium precipitation type battery is known in which metallic lithium is precipitated on the negative electrode current collector during charging (see, for example, Patent Document 1). In the charging process of such a lithium precipitation type all-solid-state lithium secondary battery, metallic lithium is precipitated between the solid electrolyte layer and the negative electrode current collector. Therefore, a space for metallic lithium to precipitate is required between the solid electrolyte layer and the negative electrode current collector. If such a space does not exist sufficiently, there are problems such as the growth of dendrites due to the precipitation of metallic lithium causing an internal short circuit, and problems such as the overvoltage when metallic lithium precipitates during the charging process becoming large and the charge / discharge rate characteristics deteriorating. Patent Document 1 attempts to prevent the occurrence of such problems by providing a lithium occlusion layer containing carbon and solid electrolyte and having a porosity of 60% or more between the solid electrolyte layer and the negative electrode current collector. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] JP 2019-33053 A Summary of the Invention [Problem to be solved by the invention]

[0008] However, according to the studies of the present inventors, it has become clear that even if the technique described in Patent Document 1 is used, there are still cases where sufficient charge / discharge rate characteristics cannot be achieved.

[0009] Therefore, an object of the present invention is to provide a means for improving the charge / discharge rate characteristics of a lithium deposition type lithium secondary battery. [Means for solving the problem]

[0010] The present inventors have conducted extensive research to solve the above problems. As a result, in a secondary battery including a lithium deposition type power generating element and a pressing member for pressing the power generating element in the stacking direction, the ten-point average roughness (R zJIS The present inventors have found that the above problems can be solved by controlling the above-mentioned temperature within a predetermined range, and have completed the present invention.

[0011] That is, one aspect of the present invention relates to a lithium secondary battery including a positive electrode having a positive electrode active material layer containing a positive electrode active material capable of absorbing and releasing lithium ions, a negative electrode having a negative electrode current collector on which lithium metal is deposited during charging, a power generating element having a solid electrolyte layer interposed between the positive electrode and the negative electrode, and a pressure member that applies a predetermined pressure to the power generating element in the stacking direction. zJIS ) is 3 to 50 μm. Effect of the Invention

[0012] According to the present invention, it is possible to improve the charge and discharge rate characteristics of a lithium deposition type lithium secondary battery. [Brief description of the drawings]

[0013] [Figure 1] 1 is a cross-sectional view showing a schematic overall structure of a stacked type (internal parallel connection type) all-solid-state lithium secondary battery according to one embodiment of the present invention. [Diagram 2] FIG. 2 is an enlarged cross-sectional view of a negative electrode current collector of the stacked secondary battery according to one embodiment of the present invention. [Diagram 3] 1 is a perspective view of a stacked secondary battery according to one embodiment of the present invention; [Figure 4] FIG. 4 is a side view seen from a direction A shown in FIG. [Diagram 5] 1 is a perspective view showing the appearance of a stacked secondary battery according to one embodiment of the present invention; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] One aspect of the present invention is a power generating element including a positive electrode having a positive electrode active material layer containing a positive electrode active material capable of absorbing and releasing lithium ions, a negative electrode having a negative electrode current collector and in which lithium metal is deposited on the negative electrode current collector during charging, and a solid electrolyte layer interposed between the positive electrode and the negative electrode, and a pressure member that presses the power generating element with a predetermined pressure in a stacking direction, and the ten-point average roughness (R zJIS ) is 3 to 50 μm. According to the lithium secondary battery of this embodiment, it is possible to improve the charge and discharge rate characteristics in a lithium precipitation type lithium secondary battery.

[0015] The present embodiment will be described below with reference to the drawings, but the technical scope of the present invention should be determined based on the description of the claims, and is not limited to the following embodiment. Note that the dimensional ratios in the drawings are exaggerated for the convenience of explanation and may differ from the actual ratios.

[0016] Fig. 1 is a cross-sectional view showing a schematic overall structure of a stacked type (internal parallel connection type) all-solid-state lithium secondary battery (hereinafter also simply referred to as a "stacked type secondary battery") according to one embodiment of the present invention. The stacked type secondary battery 10a shown in Fig. 1 has a structure in which a substantially rectangular power generating element 21, in which a charge / discharge reaction actually proceeds, is sealed inside a laminate film 29 that is a battery exterior body. Note that a restraining pressure is applied to the stacked type secondary battery 10a in the stacking direction of the power generating element 21 by a pressure member (not shown). Therefore, the volume of the power generating element 21 is kept constant.

[0017] As shown in FIG. 1, a power generating element 21 of a stacked secondary battery 10a of this embodiment has a configuration in which a negative electrode in which a carbon layer 13 containing Ketjen Black (registered trademark) and a solid electrolyte is arranged on both sides of a negative electrode current collector 11′, a solid electrolyte layer 17, and a positive electrode in which a positive electrode active material layer 15 containing a lithium transition metal composite oxide is arranged on both sides of a positive electrode current collector 11″ are stacked. Specifically, the negative electrode, the solid electrolyte layer, and the positive electrode are stacked in this order such that one carbon layer 13 and an adjacent positive electrode active material layer 15 face each other with the solid electrolyte layer 17 interposed therebetween. As a result, the adjacent negative electrode, solid electrolyte layer, and positive electrode constitute one unit cell layer 19. Therefore, the stacked secondary battery 10a shown in FIG. 1 can be said to have a configuration in which a plurality of unit cell layers 19 are stacked and electrically connected in parallel.

[0018] A negative current collector 25 and a positive current collector 27 which are electrically connected to the electrodes (negative and positive) are attached to the negative current collector 11' and the positive current collector 11", respectively, and are structured to be sandwiched between the ends of the laminate film 29 and led out of the laminate film 29. The negative current collector 25 and the positive current collector 27 may be attached to the negative current collector 11' and the positive current collector 11" of the electrodes by ultrasonic welding, resistance welding, or the like, respectively, via a negative terminal lead and a positive terminal lead (not shown) as necessary.

[0019] In the above description, an embodiment of the all-solid-state battery according to the present invention has been described using a stacked type (internal parallel connection type) all-solid-state lithium secondary battery as an example. However, the type of all-solid-state battery to which the present invention can be applied is not particularly limited, and the present invention can also be applied to a bipolar type all-solid-state battery.

[0020] 2 is an enlarged cross-sectional view of a negative electrode current collector of a stacked secondary battery according to one embodiment of the present invention. As shown in FIG. 2, in a stacked secondary battery 10a according to this embodiment, the surface of the negative electrode current collector 11' on the side of the solid electrolyte layer 17 is not flat, and a large number of protrusions 11a are present on this surface. Specifically, the surface of the negative electrode current collector 11' on the side of the solid electrolyte layer 17 has a ten-point average roughness (R zJISThe roughness has a range of 3 to 50 μm. zJIS The ten-point average roughness (R ) is calculated by taking a reference length from the roughness curve in the direction of the average line, and then measuring from the average line of this taken portion in the direction of the longitudinal magnification, and calculating the sum of the average of the absolute values ​​of the elevations (Yp) of the five highest peaks and the average of the absolute values ​​of the elevations (Yv) of the five lowest valleys, and expressing this value in micrometers (μm). zJIS ) was called Rz in the previous JIS standard, but it has been deleted from the current JIS standard. However, since the measurement method is described in Annex JA of JIS B 0601-2013, the values ​​measured in accordance with this method will be used in the present invention.

[0021] In the embodiment shown in FIG. 2, a sputtering layer 12 (thickness 30 nm) of tin (Sn), which is a metal that can be alloyed with lithium, is provided as a lithium alloying metal layer on the surface of the negative electrode current collector 11′ facing the solid electrolyte layer 17.

[0022] Fig. 3 is a perspective view of a stacked secondary battery according to one embodiment of the present invention, Fig. 4 is a side view seen from a direction A shown in Fig. 3.

[0023] As shown in Fig. 3 and Fig. 4, the stacked secondary battery 100 according to this embodiment includes the power generating element 21 sealed in the laminate film 29 shown in Fig. 1, two metal plates 200 sandwiching the power generating element 21 sealed in the laminate film 29, and a bolt 300 and a nut 400 as fastening members. The fastening members (bolt 300 and nut 400) have a function of fixing the power generating element 21 sealed in the laminate film 29 in a sandwiched state between the metal plates 200. As a result, the metal plates 200 and the fastening members (bolt 300 and nut 400) function as pressure members that press (restrain) the power generating element 21 in its stacking direction. The pressure members are not particularly limited as long as they are members that can press the power generating element 21 in its stacking direction. As the pressure members, a combination of a plate made of a material having rigidity such as the metal plate 200 and the above-mentioned fastening members is typically used. As for the fastening members, in addition to the bolts 300 and nuts 400, tension plates or the like that fix the ends of the metal plates 200 so as to restrain the power generating element 21 in the stacking direction may be used.

[0024] The lower limit of the load (restraint pressure in the stacking direction of the power generating element) applied to the power generating element 21 is, for example, 0.1 MPa or more, preferably 1 MPa or more, and more preferably 5 MPa or more. The upper limit of the restraint pressure in the stacking direction of the power generating element is, for example, 100 MPa or less, preferably 90 MPa or less, and more preferably 80 MPa or less.

[0025] The main components of the above-mentioned stacked secondary battery 10a will now be described.

[0026] [Positive electrode current collector] The positive electrode current collector is a conductive member that functions as a flow path for electrons that are discharged from the positive electrode toward an external load or flow from a power source toward the positive electrode as the battery reaction (charge / discharge reaction) progresses. There are no particular limitations on the material that constitutes the positive electrode current collector. For example, metals and conductive resins can be used as the material that constitutes the positive electrode current collector.

[0027] Specifically, the metal may be aluminum, nickel, iron, stainless steel, titanium, copper, etc. In addition to these, a clad material of nickel and aluminum, a clad material of copper and aluminum, etc. may be used. Also, a foil in which a metal surface is coated with aluminum may be used. Among them, aluminum, stainless steel, copper, and nickel are preferable from the viewpoint of electronic conductivity, battery operating potential, etc.

[0028] The latter conductive resin may be a resin obtained by adding a conductive filler to a non-conductive polymeric material as required.

[0029] Examples of non-conductive polymeric materials include polyethylene (PE; high density polyethylene (HDPE), low density polyethylene (LDPE), etc.), polypropylene (PP), polyethylene terephthalate (PET), polyethernitrile (PEN), polyimide (PI), polyamideimide (PAI), polyamide (PA), polytetrafluoroethylene (PTFE), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyvinyl chloride (PVC), polyvinylidene fluoride (PVdF), polystyrene (PS), etc. Such non-conductive polymeric materials can have excellent electric potential resistance or solvent resistance.

[0030] A conductive filler may be added to the conductive polymer material or non-conductive polymer material as necessary. In particular, when the resin serving as the base material of the current collector is made of only a non-conductive polymer, a conductive filler is necessarily required to impart conductivity to the resin.

[0031] The conductive filler can be used without any particular limitation as long as it is a material having electrical conductivity. For example, metals and conductive carbons can be mentioned as materials having excellent electrical conductivity, potential resistance, or lithium ion blocking properties. The metal is not particularly limited, but preferably contains at least one metal selected from the group consisting of Ni, Ti, Al, Cu, Pt, Fe, Cr, Sn, Zn, In, and Sb, or an alloy or metal oxide containing these metals. The conductive carbon is also not particularly limited. Preferably, it contains at least one selected from the group consisting of acetylene black, Vulcan (registered trademark), Black Pearl (registered trademark), carbon nanofiber, Ketjen Black (registered trademark), carbon nanotube, carbon nanohorn, carbon nanoballoon, and fullerene.

[0032] The amount of conductive filler added is not particularly limited as long as it is an amount that can impart sufficient conductivity to the current collector, and is generally 5 to 80 mass % relative to the total mass of the current collector (100 mass %).

[0033] The current collector may be a single layer structure made of a single material, or may be a laminate structure made of a suitable combination of layers made of these materials. From the viewpoint of reducing the weight of the current collector, it is preferable that the current collector includes at least a conductive resin layer made of a resin having electrical conductivity. In addition, from the viewpoint of blocking the movement of lithium ions between the single cell layers, a metal layer may be provided on a part of the current collector.

[0034] The thickness of the positive electrode current collector is not particularly limited, but is, for example, 10 to 100 μm.

[0035] [Cathode active material layer] The positive electrode constituting the lithium secondary battery according to this embodiment has a positive electrode active material layer containing a positive electrode active material capable of absorbing and releasing lithium ions. The positive electrode active material layer 15 is typically disposed on the surface of a positive electrode current collector 11" as shown in FIG. 1, but in cases where the positive electrode active material layer 15 itself has a certain degree of conductivity, it is also possible for the positive electrode active material layer itself to constitute the positive electrode without using a positive electrode current collector.

[0036] The positive electrode active material is not particularly limited as long as it is a material that can release lithium ions during the charging process of the secondary battery and absorb lithium ions during the discharging process. An example of such a positive electrode active material is one that contains an M1 element and an O element, and the M1 element contains at least one element selected from the group consisting of Li, Mn, Ni, Co, Cr, Fe, and P. Examples of such a positive electrode active material include layered rock salt type active materials such as LiCoO2, LiMnO2, LiNiO2, and Li(Ni-Mn-Co)O2, LiMn2O4, LiNi 0.5 Mn 1.5 Examples of oxide active materials other than those mentioned above include spinel-type active materials such as LiFePO4 and LiMnPO4, olivine-type active materials such as Li2FeSiO4 and Li2MnSiO4, and Si-containing active materials such as Li4Ti5O 12 , LiVO2.

[0037] In some cases, two or more kinds of positive electrode active materials may be used in combination. Of course, positive electrode active materials other than those mentioned above may also be used.

[0038] In a preferred embodiment, the positive electrode active material layer 15 constituting the lithium secondary battery according to this embodiment contains a layered rock salt type active material containing lithium and cobalt (e.g., Li(Ni-Mn-Co)O2) as a positive electrode active material from the viewpoint of output characteristics.

[0039] The shape of the positive electrode active material may be, for example, particulate (spherical, fibrous), thin film, etc. When the positive electrode active material is particulate, its average particle diameter (D 50 ) is, for example, preferably in the range of 1 nm to 100 μm, more preferably in the range of 10 nm to 50 μm, further preferably in the range of 100 nm to 20 μm, and particularly preferably in the range of 1 to 20 μm. In this specification, the average particle diameter (D 50 The value of can be measured by a laser diffraction scattering method.

[0040] The content of the positive electrode active material in the positive electrode active material layer is not particularly limited, but is, for example, preferably in the range of 30 to 99 mass %, more preferably in the range of 40 to 90 mass %, and even more preferably in the range of 45 to 80 mass %.

[0041] In the lithium secondary battery according to this embodiment, the positive electrode active material layer 15 preferably further contains a solid electrolyte. Examples of the solid electrolyte include a sulfide solid electrolyte, a resin solid electrolyte, and an oxide solid electrolyte. As the solid electrolyte, a material having a desired bulk modulus can be appropriately selected according to the degree of volume expansion accompanying charge and discharge of the electrode active material used.

[0042] In a preferred embodiment of the secondary battery according to the present invention, the solid electrolyte preferably includes a resin solid electrolyte, from the viewpoint of being able to better follow the volume change of the electrode active material accompanying charge and discharge. Examples of such a resin solid electrolyte include fluororesin, polyethylene oxide, polyacrylonitrile, polyacrylate, and derivatives and copolymers thereof.

[0043] Examples of fluororesins include those containing vinylidene fluoride (VdF), hexafluoropropylene (HFP), tetrafluoroethylene (TFE), and derivatives thereof as structural units. Specific examples include homopolymers such as polyvinylidene fluoride (PVdF), polyhexafluoropropylene (PHFP), and polytetrafluoroethylene (PTFE), and binary copolymers such as a copolymer of VdF and HFP.

[0044] In another preferred embodiment of the secondary battery according to this embodiment, from the viewpoint that the solid electrolyte can better follow the volume change of the electrode active material accompanying charge and discharge, it is preferably a sulfide solid electrolyte containing S element, more preferably a sulfide solid electrolyte containing Li element, M element and S element, and the M element is a sulfide solid electrolyte containing at least one element selected from the group consisting of P, Si, Ge, Sn, Ti, Zr, Nb, Al, Sb, Br, Cl and I, and more preferably a sulfide solid electrolyte containing S element, Li element and P element.

[0045] The sulfide solid electrolyte may have a Li3PS4 skeleton, a Li4P2S7 skeleton, or a Li4P2S6 skeleton. Examples of the sulfide solid electrolyte having a Li3PS4 skeleton include LiI-Li3PS4 and LiI-LiBr-Li3PS 4、 Li3PS4. Examples of the sulfide solid electrolyte having a Li4P2S7 skeleton include, for example, a Li-P-S based solid electrolyte called LPS. Further, as the sulfide solid electrolyte, for example, Li (4-x) Ge (1-x) P x S4 (where x satisfies 0 < x < 1), such as LGPS, may be used. More specifically, for example, LPS (Li2S-P2S5), Li7P3S 11 , Li 3.2 P 0.96 S, Li 3.25 Ge 0.25 P 0.75 S4, Li 10 GeP2S 12 , or Li6PS5X (where X is Cl, Br or I), etc. can be mentioned. Note that the description of "Li2S-P2S5" means a sulfide solid electrolyte formed using a raw material composition containing Li2S and P2S5, and the same applies to other descriptions. Among them, from the viewpoint that the sulfide solid electrolyte has high ionic conductivity and low volume elastic modulus and can follow the volume change of the electrode active material accompanying charge and discharge, preferably LPS (Li2S-P2S5), Li6PS5X (where X is Cl, Br or I), Li7P3S 11 , Li 3.2 P0.96 S and Li3PS4.

[0046] The content of the solid electrolyte in the positive electrode active material layer is not particularly limited, but is, for example, preferably in the range of 1 to 70 mass %, more preferably in the range of 10 to 60 mass %, and even more preferably in the range of 20 to 55 mass %.

[0047] (Conductive additives and binders) The positive electrode active material layer may further contain at least one of a conductive assistant and a binder in addition to the positive electrode active material and the solid electrolyte. However, in a preferred embodiment, the positive electrode active material layer does not contain a binder, and in a more preferred embodiment, the positive electrode active material layer does not contain a conductive assistant and a binder.

[0048] Examples of the conductive assistant include metals such as aluminum, stainless steel (SUS), silver, gold, copper, and titanium, alloys or metal oxides containing these metals; carbon fibers (specifically, vapor-grown carbon fibers (VGCF), polyacrylonitrile-based carbon fibers, pitch-based carbon fibers, rayon-based carbon fibers, activated carbon fibers, etc.), carbon nanotubes (CNTs), and carbon black (specifically, acetylene black, Ketjen Black (registered trademark), furnace black, channel black, thermal lamp black, etc.), but are not limited thereto. In addition, a particulate ceramic material or a resin material coated with the above-mentioned metal material by plating or the like can also be used as a conductive assistant. Among these conductive assistants, from the viewpoint of electrical stability, it is preferable to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, copper, titanium, and carbon, more preferably to include at least one selected from the group consisting of aluminum, stainless steel, silver, gold, and carbon, and even more preferably to include at least one carbon. These conductive assistants may be used alone or in combination of two or more.

[0049] The conductive assistant is preferably in the form of particles or fibers. When the conductive assistant is in the form of particles, the shape of the particles is not particularly limited, and may be any shape such as powder, sphere, rod, needle, plate, column, irregular shape, scale, spindle shape, etc.

[0050] When the conductive assistant is particulate, the average particle diameter (primary particle diameter) is not particularly limited, but is preferably 0.01 to 10 μm from the viewpoint of the electrical properties of the battery. In this specification, the "particle diameter of the conductive assistant" means the maximum distance L between any two points on the contour line of the conductive assistant. The value of the "average particle diameter of the conductive assistant" is calculated as the average value of particle diameters of particles observed in several to several tens of fields of view using an observation means such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0051] When the positive electrode active material layer contains a conductive assistant, the content of the conductive assistant in the positive electrode active material layer is not particularly limited, but is preferably 0 to 10 mass%, more preferably 2 to 8 mass%, and further preferably 4 to 7 mass% relative to the total mass of the positive electrode active material layer. If the content is within such a range, a stronger electron conduction path can be formed in the positive electrode active material layer, which can effectively contribute to improving the battery characteristics.

[0052] The thickness of the positive electrode active material layer differs depending on the intended configuration of the all-solid-state battery, but is preferably within the range of, for example, 0.1 to 1000 μm.

[0053] From the viewpoint of improving the energy density of the secondary battery, the porosity of the positive electrode active material layer is preferably 20% or less, more preferably 18% or less, and further preferably 15% or less. The lower limit is not particularly limited, but is preferably 5% or more.

[0054] [Solid electrolyte layer] The solid electrolyte layer is a layer interposed between the positive electrode active material layer and the negative electrode current collector, and contains a solid electrolyte (usually as a main component). The specific form of the solid electrolyte contained in the solid electrolyte layer is the same as that described above, so a detailed description will be omitted here.

[0055] The content of the solid electrolyte in the solid electrolyte layer is, for example, preferably in the range of 10 to 100 mass%, more preferably in the range of 50 to 100 mass%, and further preferably in the range of 90 to 100 mass%, relative to the total mass of the solid electrolyte layer.

[0056] The solid electrolyte layer may further contain a binder in addition to the above-mentioned solid electrolyte.

[0057] The thickness of the solid electrolyte layer differs depending on the intended configuration of the all-solid-state battery, but is preferably within the range of, for example, 0.1 to 1000 μm.

[0058] [Negative electrode current collector] The negative electrode current collector is a conductive member that functions as a flow path for electrons that are discharged from the negative electrode to the power source or flow from an external load to the negative electrode as the battery reaction (charge / discharge reaction) progresses. There are no particular limitations on the material that constitutes the negative electrode current collector. For example, metals and conductive resins can be used as the material that constitutes the negative electrode current collector.

[0059] As described above with reference to FIG. 2, the negative electrode current collector 11′ has a ten-point average roughness (R zJIS ) is 3 to 50 μm. From the viewpoints that such roughness can be easily achieved and that the roughness can be maintained for a long period of time even under the restraining pressure applied by the pressing member, it is preferable that the material constituting the negative electrode current collector is a metal. Specific examples of metals include nickel, stainless steel, titanium, and copper. Among them, stainless steel, copper, and nickel are preferable from the viewpoints of electronic conductivity, battery operating potential, and the like.

[0060] The thickness of the negative electrode current collector is not particularly limited, but is, for example, 10 to 100 μm. zJIS The value of the ten-point average roughness (R zJIS There is no particular limitation on the method for controlling the value of (a) to within such a range, and any conventionally known method for roughening (roughening) the surface of a metal foil can be appropriately adopted. Examples of such roughening (roughening) the surface of a metal foil include an up-method such as a granulation process and a down-method such as an etching process and a polishing process.

[0061] According to the lithium secondary battery of the present embodiment, in a lithium secondary battery including a so-called lithium precipitation type power generating element and a pressing member for pressing the power generating element with a predetermined pressure in the stacking direction, the ten-point average roughness (R zJIS By controlling the ten-point mean roughness (R zJIS ) is relatively large at 3 μm or more, so that a sufficient space is secured between the negative electrode current collector and the solid electrolyte layer for lithium metal to precipitate during charging. As a result, it is considered that an increase in overvoltage during lithium metal precipitation is suppressed, and charge / discharge rate characteristics are improved. In addition, the above-mentioned space absorbs to some extent the volume change of the negative electrode caused by lithium precipitation during charging, so that lithium metal can be uniformly precipitated on the negative electrode current collector, which is also considered to contribute to the improvement of charge / discharge rate characteristics. In other words, it is presumed that the reason why sufficient charge / discharge rate characteristics could not be achieved even with the technology described in the above-mentioned Patent Document 1 is that the volume change of the negative electrode caused by lithium precipitation during charging could not be sufficiently alleviated. Note that, in the lithium secondary battery according to this embodiment, the above-mentioned ten-point average roughness (R zJIS The upper limit of R zJISIf the value exceeds 50 μm, it becomes difficult to achieve uniform deposition of lithium metal on the negative electrode current collector during charging.

[0062] In the lithium secondary battery according to this embodiment, the negative electrode current collector may be curved. By curving the negative electrode current collector, it may be possible to arrange a larger space for holding the lithium metal deposited during the charging process. The direction of the curvature is not particularly limited, and the center of the negative electrode current collector may protrude or be recessed toward the solid electrolyte layer. The degree of curvature is not particularly limited, but the displacement height (the maximum distance of the negative electrode current collector in the stacking direction of the power generating element) may be about 3 to 50 μm.

[0063] Furthermore, as described above with reference to FIG. 2, it is preferable that a lithium alloying metal layer (a tin (Sn) sputtering layer 12 shown in FIG. 2) containing a metal that can be alloyed with lithium is disposed on the surface of the negative electrode current collector 11' on the side of the solid electrolyte layer 17. Examples of metals that can be alloyed with lithium include aluminum, magnesium, zinc, bismuth, tin, lead, indium, ruthenium, rhodium, iridium, palladium, platinum, silver, gold, cadmium, gallium, thallium, silicon, and germanium. Among these, from the viewpoint of being able to configure a battery with excellent capacity and energy density, it is preferable that the material that can be alloyed with lithium contains at least one metal selected from the group consisting of magnesium, silver, silicon, gold, indium, germanium, tin, lead, aluminum, and zinc, and more preferably contains magnesium, tin, silver, silicon, gold, or indium.

[0064] The thickness of the lithium alloying metal layer is not particularly limited, but is preferably about 10 nm to 10 μm. The specific method for disposing the lithium alloying metal layer on the surface of the negative electrode current collector is also not particularly limited, and examples thereof include dry methods such as sputtering, and wet methods in which a slurry containing fine particles of a metal that can be alloyed with lithium is applied and dried.

[0065] According to the above-mentioned configuration, the lithium ions that reach the negative electrode side through the solid electrolyte layer during charging of the lithium secondary battery are alloyed with a metal that can be alloyed with lithium. The lithium-containing alloy is then held in the space present on the surface of the negative electrode current collector. Compared to when metallic lithium is precipitated as a single substance, the precipitation energy is smaller when the lithium-containing alloy is precipitated, so that the above-mentioned configuration allows metallic lithium to be precipitated more uniformly. In addition, the interface resistance between the negative electrode current collector and the solid electrolyte layer is also reduced, making it possible to achieve a higher current density. As a result, the charge / discharge rate characteristics can be further improved.

[0066] As described above with reference to FIG. 1, it is preferable that a carbon layer containing non-graphite carbon is disposed on the surface of the negative electrode current collector 11' on the side of the solid electrolyte layer 17. With such a configuration, bulky and highly conductive carbon is disposed between the negative electrode current collector and the solid electrolyte layer. As a result, the contact area between the solid electrolyte layer and the negative electrode current collector can be increased to reduce the contact resistance at the interface between them while minimizing the reduction in the space for lithium metal to precipitate during the charging process, which can contribute to further improving the charge / discharge rate characteristics. If highly crystalline graphite is used for the carbon layer, it may be oriented on the negative electrode current collector and easily peel off. On the other hand, by using non-graphite carbon for the carbon layer, peeling of the carbon layer from the negative electrode current collector can be suppressed.

[0067] Examples of non-graphite carbon used to form the carbon layer include Ketjen Black (registered trademark), vapor grown carbon fiber (VGCF), acetylene black, activated carbon, furnace black, carbon nanotubes (CNT), graphene, etc., among which Ketjen Black (registered trademark) is preferred. In the case of Ketjen Black (registered trademark), lithium ions are unlikely to be inserted between the layers, so that charging and discharging is unlikely to proceed at a potential more noble than the deposition and dissolution potential of metallic lithium, which can contribute to improving the energy density of the battery. The average particle size (D50) of the non-graphite carbon is preferably within the range of, for example, 10 nm to 10 μm, and more preferably within the range of 15 nm to 5 μm. The value of the average particle size of the non-graphite carbon can be calculated using a laser diffraction particle size distribution meter, or measured based on image analysis using an electron microscope such as SEM.

[0068] The carbon layer may further include the above-mentioned solid electrolyte. The ratio of carbon to the solid electrolyte in the carbon layer is preferably 1:1 to 10:0, more preferably 2:1 to 10:0, in terms of the mass ratio of these two materials. There is also no particular limitation on the method of forming the carbon layer. For example, the mixture obtained by hand mixing using a mortar and pestle, homogenizer, mechanical milling, etc. may be wet-applied, or the mixture may be molded into the shape of the carbon layer by powder compaction similar to that of the positive electrode active material layer.

[0069] In the above-mentioned carbon layer, the surface of the non-graphite carbon constituting the carbon layer is preferably coated with a metal capable of being alloyed with lithium. This configuration can further increase the contact area between the solid electrolyte layer and the negative electrode current collector, and can also substantially increase the electrode area, which has the advantage of further improving the charge / discharge rate characteristics. Here, an example of a configuration in which "the surface of the non-graphite carbon is coated with a metal capable of being alloyed with lithium" is a configuration in which a lithium alloying metal layer containing a metal capable of being alloyed with lithium is provided on the surface of the above-mentioned carbon layer on the side of the solid electrolyte layer. In addition, a configuration in which the surface of the non-graphite carbon before the carbon layer is formed is coated with a metal capable of being alloyed with lithium by plating or the like and then used to form the above-mentioned carbon layer can also be adopted.

[0070] [Positive and negative current collectors] The material constituting the current collector plates (25, 27) is not particularly limited, and any known highly conductive material conventionally used as a current collector plate for a secondary battery may be used. As the material constituting the current collector plates, for example, metal materials such as aluminum, carbon-coated aluminum, copper, titanium, nickel, stainless steel (SUS), and alloys thereof are preferable. From the viewpoints of light weight, corrosion resistance, and high conductivity, aluminum and copper are more preferable, and aluminum is particularly preferable. The negative electrode current collector plate 25 and the positive electrode current collector plate 27 may be made of the same material or different materials.

[0071] [Positive and negative leads] Although not shown in the figures, the current collectors (11", 11') and the current collecting plates (27, 25) may be electrically connected via positive and negative electrode leads. As the materials for the positive and negative electrode leads, materials used in known lithium secondary batteries may be used. Note that the parts removed from the exterior are preferably covered with a heat-resistant insulating heat-shrink tube or the like to prevent them from coming into contact with peripheral devices or wiring, causing electric leakage and affecting products (e.g., automobile parts, particularly electronic devices, etc.).

[0072] [Battery exterior] As the battery exterior body, a known metal can case can be used, and a bag-shaped case using a laminate film 29 containing aluminum, which can cover the power generating element as shown in FIG. 1, can be used. The laminate film can be, for example, a three-layer laminate film formed by laminating PP, aluminum, and nylon in this order, but is not limited thereto. A laminate film is preferable from the viewpoint of being excellent in high output and cooling performance and being suitable for use in batteries for large equipment such as EVs and HEVs. In addition, a laminate film containing aluminum is more preferable as the exterior body because it can easily adjust the group pressure applied to the power generating element from the outside.

[0073] FIG. 5 is a perspective view showing the appearance of a stacked secondary battery according to one embodiment of the present invention. As shown in FIG. 5, a flat stacked secondary battery 50 has a rectangular flat shape, and a positive electrode tab 58 and a negative electrode tab 59 for taking out electric power are pulled out from both sides. A power generating element 57 is wrapped in a battery exterior body (laminate film 52) of the stacked secondary battery 50, and the periphery is heat-sealed, and the power generating element 57 is sealed in a state in which the positive electrode tab 58 and the negative electrode tab 59 are pulled out to the outside. Here, the power generating element 57 corresponds to the power generating element 21 of the stacked secondary battery 10a shown in FIG. 1 described above. The power generating element 57 is formed by stacking a plurality of unit cell layers (single cells) 19 each composed of a positive electrode (positive electrode current collector 11″ and positive electrode active material layer 15), a solid electrolyte layer 17, and a negative electrode (negative electrode current collector 11′).

[0074] The lithium secondary battery according to this embodiment is not limited to a flat shape. A wound-type all-solid-state battery may be cylindrical, or may be a cylindrical shape that has been deformed to have a rectangular flat shape, and is not particularly limited. In the above-mentioned cylindrical shape, a laminate film may be used for the exterior body, or a conventional cylindrical can (metal can) may be used, and is not particularly limited. Preferably, the power generating element is exteriorized with an aluminum laminate film. This form can achieve weight reduction. Also, there is no particular restriction on the removal of the tabs 58 and 59 shown in FIG. 5. The positive electrode tab 58 and the negative electrode tab 59 may be pulled out from the same side, or the positive electrode tab 58 and the negative electrode tab 59 may be divided into a plurality of tabs and taken out from each side, and are not limited to those shown in FIG. Also, in a wound-type all-solid-state battery, a cylindrical can (metal can) may be used instead of the tab to form the terminal.

[0075] The above description has been given with reference to an example in which the secondary battery according to the present embodiment is an all-solid-state lithium secondary battery, but the lithium secondary battery according to the present embodiment does not have to be an all-solid-state type. That is, the solid electrolyte layer may further contain a conventionally known liquid electrolyte (electrolytic solution). There is no particular restriction on the amount of liquid electrolyte (electrolytic solution) that can be contained in the solid electrolyte layer, but it is preferable that the amount is such that the shape of the solid electrolyte layer formed by the solid electrolyte is maintained and the liquid electrolyte (electrolytic solution) does not leak. As the liquid electrolyte (electrolytic solution), a solution having a form in which a conventionally known lithium salt is dissolved in a conventionally known organic solvent is used. The liquid electrolyte (electrolytic solution) may further contain additives other than the organic solvent and the lithium salt. These additives may be used alone or in combination of two or more. In addition, the amount of additives used in the electrolyte solution can be appropriately adjusted.

[0076] [Battery pack] A battery pack is a device that consists of multiple batteries connected together. More specifically, it is a device that uses at least two batteries and is configured in series or parallel or both. By connecting them in series or parallel, it is possible to freely adjust the capacity and voltage.

[0077] A small, removable assembled battery can be formed by connecting a plurality of batteries in series or in parallel. A large-capacity, high-output assembled battery suitable for use as a vehicle driving power source or an auxiliary power source, which require a high volumetric energy density and a high volumetric output density, can be formed by further connecting a plurality of such small, removable assembled batteries in series or in parallel. How many batteries are connected to form an assembled battery, and how many stages of small assembled batteries are stacked to form a large-capacity assembled battery, can be determined according to the battery capacity and output of the vehicle (electric vehicle) in which the battery is to be installed.

[0078] [vehicle] The lithium secondary battery according to the present embodiment has a high energy density per volume. In vehicle applications such as electric vehicles, hybrid electric vehicles, fuel cell vehicles, and hybrid fuel cell vehicles, higher capacity and larger size are required compared to electric and portable electronic device applications. Therefore, the all-solid-state battery according to the present embodiment can be suitably used as a power source for vehicles, for example, a power source for driving a vehicle or an auxiliary power source.

[0079] Specifically, a battery or a battery pack formed by combining a plurality of batteries can be mounted on a vehicle. In the present invention, a high-capacity battery with excellent output characteristics can be configured, and thus, by mounting such a battery, a plug-in hybrid electric vehicle with a long EV driving distance or an electric vehicle with a long driving distance per charge can be configured. For example, a battery or a battery pack formed by combining a plurality of batteries can be used in a hybrid vehicle, a fuel cell vehicle, or an electric vehicle (all of which include four-wheeled vehicles (commercial vehicles such as passenger cars, trucks, and buses, and light vehicles, etc.), as well as two-wheeled vehicles (motorcycles) and three-wheeled vehicles) to make the vehicle have a long driving distance. However, the use is not limited to automobiles, and the battery pack can be applied to, for example, various power sources for other vehicles, such as moving bodies such as trains, and can also be used as a mounted power source for an uninterruptible power supply device or the like. EXAMPLES

[0080] The present invention will be described in more detail below with reference to examples. However, the technical scope of the present invention is not limited to the following examples. In the following, the operations were performed in a glove box. Furthermore, the instruments and devices used in the glove box were thoroughly dried in advance.

[0081] <Comparative Example 1> (Preparation of Positive Electrode Mixture) LiNi as the positive electrode active material 0.8 Mn 0.1 Co 0.1 A certain amount of O2, LPS (Li2S-P2S5) as a solid electrolyte, and acetylene black as a conductive additive were weighed out, and beads were further added and mixed with a roller to obtain a positive electrode mixture. The compounding ratio (mass ratio) of each component was positive electrode active material: solid electrolyte: conductive additive = 60:34:6.

[0082] (Preparation of evaluation cells) The positive electrode mixture prepared above and a negative electrode current collector were placed opposite each other with a solid electrolyte layer interposed therebetween to prepare an evaluation cell (lithium precipitation type all-solid-state lithium secondary battery).

[0083] Specifically, 100 mg of LPS (Li2S-P2S5) was weighed out, placed in a ceramic tube, and the surface was smoothed. Then, a pressure of 400 MPa was applied using a fastening jig to produce a solid electrolyte pellet (φ10 mm).

[0084] Thereafter, the fastening jig was removed, and a predetermined amount of the positive electrode mixture was placed on one side of the pellet, and the positive electrode active material layer was prepared by applying a pressure of 200 [MPa] using the fastening jig. Nickel foil (smooth surface type NIF L, thickness 20 μm, manufactured by Fukuda Metal Foil and Powder Co., Ltd.) was placed as a negative electrode current collector on the other side of the pellet, and the fastening jig was applied with a pressure of 100 [MPa] to prepare an evaluation cell. The evaluation cell thus prepared was then restrained with a restraining pressure of 65 [MPa] using the fastening jig to prepare an evaluation cell for this comparative example. The ten-point average roughness (R zJIS ) was measured according to the method described in Appendix JA of JIS B 0601-2013 and was found to be 2 μm. The thickness of the positive electrode active material layer was 25 μm.

[0085] (Observation of the positive electrode active material layer after charging and discharging the battery) The all-solid-state lithium secondary battery prepared above was subjected to one cycle of charge and discharge under the following charge and discharge test conditions.

[0086] (Charge / discharge test conditions) 1) Charge / discharge conditions [Voltage range] 2.5~4.2V [Charging process]CCCV [Discharge process]CCCV [Charge / discharge rate] 0.05C, 0.2C or 1.0C (increased sequentially) (After charging and discharging, rest for 30 minutes each.) 2) Evaluation temperature: 298K (25℃).

[0087] The evaluation cell was charged from 2.5V to 4.2V at 0.05C in constant current / constant voltage (CCCV) mode in the charging process (lithium metal precipitates on the negative electrode current collector) in a thermostatic chamber set to the above evaluation temperature using a charge / discharge tester. Then, in the discharging process (lithium metal on the negative electrode current collector dissolves), the cell was discharged from 4.2V to 2.5V at 0.05C in constant current / constant voltage (CCCV) mode. If no abnormality (sudden decrease in capacity) was observed during charging / discharging at 0.05C, a similar charge / discharge test was performed at a rate of 0.2C. If no abnormality was observed during charging / discharging at 0.2C, a similar charge / discharge test was performed at a rate of 1.0C. Here, 1C refers to the current value at which the battery is fully charged (100% charged) when charged at that current value for 1 hour.

[0088] As a result of the above, in this comparative example, a rapid decrease in capacity was confirmed during the charging process at 0.05C, so the charge / discharge test was stopped. This is thought to be because the use of a smooth-surface type negative electrode current collector resulted in insufficient space for lithium metal to precipitate between the negative electrode current collector and the solid electrolyte layer during the charging process, resulting in an increase in overvoltage during lithium metal precipitation. It is also thought that lithium precipitation during the charging process caused a volume change in the negative electrode, preventing lithium metal from being uniformly precipitated on the negative electrode current collector.

[0089] <Comparative Example 2> An evaluation cell for this comparative example (lithium precipitation type all-solid-state lithium secondary battery) was produced in the same manner as in the above-mentioned Comparative Example 1, except that a sputtering layer (thickness: 30 nm) made of magnesium, which is a metal that can be alloyed with lithium, was formed by sputtering on the surface of the above-mentioned nickel foil on the solid electrolyte layer side, and used as a negative electrode current collector.

[0090] The evaluation cell prepared above was subjected to a charge-discharge test in the same manner as above. As a result, a rapid decrease in capacity was confirmed during charging at 0.05 C in this comparative example as well, so the charge-discharge test was discontinued.

[0091] <Example 1> An evaluation cell (lithium deposition type all-solid-state lithium secondary battery) for this example was produced in the same manner as in Comparative Example 1, except that nickel foil (manufactured by Fukuda Metal Foil & Powder Co., Ltd., surface roughened type NIF-MT, thickness 20 μm) was used as the negative electrode current collector. The ten-point average roughness (R zJIS ) was measured according to the method described in Appendix JA of JIS B 0601-2013 and was found to be 10 μm.

[0092] The evaluation cell prepared above was subjected to a charge / discharge test in the same manner as above. As a result, in this example, no rapid decrease in capacity was observed in the charge / discharge test at 0.05 C, but a rapid decrease in capacity was observed during the charging process at 0.2 C, so the charge / discharge test was stopped at that point.

[0093] <Example 2> An evaluation cell of this example (lithium precipitation type all-solid-state lithium secondary battery) was produced in the same manner as in Example 1 described above, except that a sputtering layer (thickness: 30 nm) made of magnesium, which is a metal that can be alloyed with lithium, was formed by sputtering on the surface of the solid electrolyte layer side of the nickel foil described above and used as a negative electrode current collector.

[0094] The evaluation cell prepared above was subjected to a charge / discharge test in the same manner as above. As a result, in this example, no rapid decrease in capacity was observed in the charge / discharge tests at 0.05 C and 0.2 C, but a rapid decrease in capacity was observed during the charging process at 1.0 C, so the charge / discharge test was stopped at that point.

[0095] <Example 3> An evaluation cell of this example (lithium precipitation type all-solid-state lithium secondary battery) was produced in the same manner as in Example 2 described above, except that a sputtering layer was formed on the surface of a negative electrode current collector using tin instead of magnesium as a metal that can be alloyed with lithium.

[0096] The evaluation cell prepared above was subjected to a charge / discharge test in the same manner as above. As a result, in this example, no rapid decrease in capacity was observed in the charge / discharge tests at 0.05 C and 0.2 C, but a rapid decrease in capacity was observed during the charging process at 1.0 C, so the charge / discharge test was stopped at that point.

[0097] <Example 4> An evaluation cell of this example (lithium precipitation type all-solid-state lithium secondary battery) was produced in the same manner as in Example 2 described above, except that silver was used instead of magnesium as a metal capable of being alloyed with lithium to form a sputtering layer on the surface of the negative electrode current collector.

[0098] The evaluation cell prepared above was subjected to a charge / discharge test in the same manner as above. As a result, in this example, no rapid decrease in capacity was observed in the charge / discharge tests at 0.05 C and 0.2 C, but a rapid decrease in capacity was observed during the charging process at 1.0 C, so the charge / discharge test was stopped at that point.

[0099] <Example 5> An evaluation cell (lithium precipitation type all-solid-state lithium secondary battery) of this example was produced in the same manner as in Example 1 described above, except that a carbon layer containing Ketjen Black (registered trademark) and a solid electrolyte was formed on the surface of the nickel foil on the solid electrolyte layer side and used as a negative electrode current collector.

[0100] Specifically, first, Ketjen Black (registered trademark) (manufactured by Lion Specialty Chemicals, ECP600JD:KB, D50=34 nm) and solid electrolyte (LPS) were weighed to a mass ratio of Ketjen Black (registered trademark):LPS=2:1, mixed by hand, added heptane, and mixed for 3 minutes using a homogenizer (manufactured by SMT Corporation, UH-50) to obtain a mixture. Next, the obtained mixture was uniformly applied to the surface of the solid electrolyte layer side of the nickel foil and dried to form a carbon layer. The thickness of the carbon layer was set to 20 μm.

[0101] The evaluation cell prepared above was subjected to a charge / discharge test in the same manner as above. As a result, in this example, no rapid decrease in capacity was observed in the charge / discharge tests at 0.05 C and 0.2 C, but a rapid decrease in capacity was observed during the charging process at 1.0 C, so the charge / discharge test was stopped at that point.

[0102] <Example 6> An evaluation cell of this example (lithium deposition type all-solid-state lithium secondary battery) was produced in the same manner as in Example 5 described above, except that a tin sputtering layer was further formed on the exposed surface (surface on the solid electrolyte layer side) of the carbon layer by using the same method as in Example 3 described above.

[0103] The evaluation cell prepared above was subjected to a charge / discharge test in the same manner as above. As a result, in this example, no rapid decrease in capacity was observed in any of the charge / discharge tests at 0.05C, 0.2C, and 1.0C.

[0104] <Example 7> An evaluation cell of this example (lithium deposition type all-solid-state lithium secondary battery) was produced in the same manner as in Example 3 described above, except that a carbon layer was further formed on the exposed surface (surface on the solid electrolyte layer side) of the tin sputtering layer by using the same method as in Example 5 described above.

[0105] The evaluation cell prepared above was subjected to a charge / discharge test in the same manner as above. As a result, in this example, no rapid decrease in capacity was observed in the charge / discharge tests at 0.05 C and 0.2 C, but a rapid decrease in capacity was observed during the charging process at 1.0 C, so the charge / discharge test was stopped at that point.

[0106] <Example 8> An evaluation cell of this example (lithium deposition type all-solid-state lithium secondary battery) was produced in the same manner as in Example 7 described above, except that a tin sputtering layer was further formed on the exposed surface (surface on the solid electrolyte layer side) of the carbon layer by using the same method as in Example 3 described above.

[0107] The evaluation cell prepared above was subjected to a charge / discharge test in the same manner as above. As a result, in this example, no rapid decrease in capacity was observed in any of the charge / discharge tests at 0.05C, 0.2C, and 1.0C.

[0108] The above results are summarized in Table 1 below.

[0109] [Table 1]

[0110] From the results shown in the above examples and comparative examples, it is understood that the charge / discharge rate characteristics of lithium precipitation type lithium secondary batteries can be improved by adopting the configuration according to the present invention. This is believed to be because the use of a surface-roughened type negative electrode current collector ensures sufficient space between the negative electrode current collector and the solid electrolyte layer for lithium metal to precipitate during the charging process, thereby suppressing the increase in overvoltage during lithium metal precipitation. In addition, it is believed that the above-mentioned space absorbs to some extent the volume change of the negative electrode caused by lithium precipitation during the charging process, thereby achieving uniform precipitation of lithium metal on the negative electrode current collector.

[0111] Furthermore, it is also found that the charge / discharge rate characteristics can be further improved by disposing a layer containing a metal that can be alloyed with lithium or by disposing a carbon layer containing non-graphitic carbon on the surface of the negative electrode current collector. [Explanation of symbols]

[0112] 10a, 50, 100 Stacked secondary battery, 11' negative electrode current collector, 11” positive electrode current collector, 11a convex portion, 12 Tin (Sn) sputtering layer, 13 carbon layer, 15 positive electrode active material layer, 17 solid electrolyte layer, 19 cell layer, 21, 57 Power generation elements, 25 negative electrode current collector (negative electrode tab), 27 Positive current collector (positive tab), 29, 52 Laminate film, 58 Positive tab, 59 negative tab, 200 metal plate, 300 volts, 400 Nuts.

Claims

1. a positive electrode having a positive electrode active material layer containing a positive electrode active material capable of absorbing and releasing lithium ions; a negative electrode having a negative electrode current collector on which lithium metal is deposited during charging; a solid electrolyte layer interposed between the positive electrode and the negative electrode and containing a solid electrolyte containing an S element; and a pressure member that applies a predetermined pressure to the power generating element in a stacking direction, The ten-point average roughness (R zJIS ) is more than 10 μm and 50 μm or less.

2. 2. The lithium secondary battery according to claim 1, wherein a lithium-alloying metal layer containing a metal capable of being alloyed with lithium is disposed on a surface of the negative electrode current collector facing the solid electrolyte layer.

3. 3. The lithium secondary battery according to claim 1, wherein a carbon layer containing non-graphitic carbon is disposed on a surface of the negative electrode current collector facing the solid electrolyte layer.

4. 4. The lithium secondary battery according to claim 3, wherein the surface of the non-graphitic carbon is coated with a metal capable of alloying with lithium.

5. The solid electrolyte contained in the solid electrolyte layer is Li 2 S-P 2 S 5 , Li 6 P.S. 5 X (wherein X is Cl, Br or I), Li 7 P 3 S 11 , Li 3.2 P 0.96 S and Li 3 P.S. 4 The lithium secondary battery according to any one of claims 1 to 4, wherein the lithium secondary battery is selected from the group consisting of:

Citation Information

Patent Citations

  • Metal lithium secondary battery

    JP1998012279A

  • Lithium secondary battery

    JP2001243957A

  • Anode for lithium metal polymer secondary battery made of anode current collector with surface patterning

    JP2006156351A

  • Lithium solid type secondary battery and method for manufacturing the same

    JP2016035867A

  • Lithium electrode and lithium secondary battery containing the same

    JP2016527679A